A uniqueness theorem for degenerate Kerr-Newman black holes - Chruściel, P; Nguyen, L (2010)
We show that the domains of dependence of stationary, $I^+$-regular, analytic, electrovacuum space-times with a connected, non-empty, rotating, degenerate event horizon arise from Kerr-Newman space-times.